(untitled) (Albayan Scientific Journal, 2023)
Ricoeur has developed his theological project as it began with problems of the human will, and then overlapped with issues of symbolic language in religious texts. He generalized interpretations of religious symbolic language to language in general by generalizing problems of literal and figurative meaning to all aspects of language. Through the subject of metaphor and the question of symbol, and how they renew language and meaning, and thus interpretation becomes necessary. Note that this is done according to established contexts and standards. This research also aims to trace the development of these issues historically or in comparison with other issues that intersect with them, or through their analysis and criticism.